Fostering Spirituality in the Workplace - Berry, Priscilla (Business Expert Press, 2013)
Ebook from IG Library ; Today, there are deep and rapid changes on companies, employees, and the global economy that should not be underestimated, and future world leaders must be prepared to lead in a manner that is socially responsible, ethical, and pro_ table. A corporation with a business model that polarizes or operates solely in the interest of its shareholders is unsustainable and current benchmarks can be unrealistic tools for businesses to rely upon as measures of future success. This book explores historical data, analyzes current events from the world stage, and delivers a worldview that challenges some existing paradigms in business. As we are living business history, the book draws from the epic economic, environmental, and cultural shifts in our collective consciousness. It begins a vital conversation by introducing some thought paradigms that will challenge current business practices, create a vision for the future, and provide a road map to navigate this uncharted territory. In the end, the author outlines specific action that you must take now to end the economic and moral decline in this first part of the 21st century.